Three Health Care Facilities and Its Practices In Pediatric Nursing: Exploring the Role and Practices of Pediatric Nurses in Health Care Facilities (Journal of Advances and Scholarly Researches in Allied Education, 2021)
To identify and categorize the nursing healthcare services provided by pediatric practices, this research looked into the activities of pediatric practice nurses. It also looked at pediatric nursing direct care for newborns, emergency nursing, psychiatric nurse specialization, and the characteristics of health care facilities, as well as two institutions with varying levels of nursing expertise. In the pediatric unit, the best practice that takes barriers into account is Health Care Facility Implementation in EBP In three HCFs, implementation of EBP has been carried out on factors associated with Nurses in the pediatric unit at three HCFs were interviewed about their work experiences. During the month-long research period, a descriptive study design was used. Out of 50 nurses, the Dilman formula chose 12, 20, and 18 nurses. The recipients were given a questionnaire that asked about five different things. This study's results highlight the possibility for the nursing profession to grow at the local level. More research is needed to examine pediatric nurses' community-based activities in greater depth.